Effect of ozonoysis pretreatment in synthesis of empty fruit bunch cellulose for bioplastic filler - Zhahidah Husna Hassan, 1996-, author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2020)
Thesis (Sarjana Kejuruteraan) - Universiti Teknologi Malaysia, 2020